Penggunaan Model Pembelajaran Teams Games Tournament (TGT) Untuk Meningkatkan Maharah Kitabah Siswa Kelas VIII SMP Takhassus Al-Qur’an Kalibeber Wonosobo - Aisyah Tresnanda; Asep Sunarko; Rifqi Aulia Rahman (AL-MUARRIB: JOURNAL OF ARABIC EDUCATION, 2022)
Arabic learning especially Maharah Kitabah at Takhassus Al-Qur'an Junior High School uses a conventional learning model. However, when the learning process takes place there are still many students who are passive, bored, and there are still many students who consider our Maharah Kitabah learning to be a difficult lesson. Therefore, it is necessary to apply a varied and interesting learning model. With the hope that the use of the Teams Games Tournament (TGT) learning model can be the solution. This research is a type of experimental research using the Nonequivalent control group design carried out at Takhassus Al-Qur'an Junior High School Caliber Wonosobo. The subject of this study was class VIII students of 56 students who were divided into two groups, namely the experimental and control groups. Data collection methods are carried out by interviewing, observation, documentation, and test methods. In the method using the test, the experimental and control groups are given written tests in the form of pretest at the beginning and postest at the end. Then the results are analyzed using the N-gain test and the t-test test to find out the comparison and difference in the ability of Maharah Kitabah between the two groups. The results of this study show that: 1) there are steps taken in the learning of Maharah Kitabah using the Teams Games Tournament (TGT) model at SMP Takhassus Al-Qur'an Caliber; 2) there is an increase in the ability of our Maharah kitabah between experimental and control groups of 0.61 which belongs to the medium category.; 3) there were differences in experimental and control groups with thitung 8,299 > ttabel 2,003. Ho is rejected and Ha is accepted